A CIA-based Sustainable Security Risk Mitigation Model for E-Certificate Systems - Teguh Nurhadi Suharsono; John Choi; Raden Ricky Agusiady; Didin Saepudin; Sukadwilinda; Heri Purwanto; Peti Savitri; Ketut Abimanyu Munastha (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
E-certificates are increasingly adopted across sectors, yet existing studies have not developed an integrated risk mitigation model that combines CIA-based sustainable security with operational and stakeholder perspectives. Current frameworks primarily address isolated technical risks or focus on general PKI security, leaving a gap in holistic modeling tailored to end-to-end e-certificate implementation. This study addresses this gap by proposing a Sustainable Security Risk Mitigation Model for e-certificate systems, guided by the CIA triad—Confidentiality, Integrity, and Availability. A mixed-methods approach was employed, including literature analysis, a Focus Group Discussion (FGD) with industry, government, and academic stakeholders, and expert evaluation using CIA-based scoring on a Likert scale. The empirical data include qualitative perspectives gathered from the FGD and quantitative assessments from expert validation. The proposed model operates in a continuous cycle consisting of risk assessment, mitigation planning, deployment and monitoring, and iterative improvement, ensuring that security controls adapt to emerging threats. Results show that the model achieves an average security validation score (asv) of 4.67, outperforming other existing risk mitigation models in CIA-based evaluation. The findings indicate that institutions can use the model as a practical framework to strengthen e-certificate governance, improve resilience against cyber threats, and support sustainable information security management.